Maximizing the acquisition of unique reads in noninvasive capture sequencing experiments. (19th December 2020) - Fontsere, Claudia; Alvarez‐Estape, Marina; Lester, Jack; Arandjelovic, Mimi; Kuhlwilm, Martin; Dieguez, Paula; Agbor, Anthony; Angedakin, Samuel; Ayuk Ayimisin, Emmanuel; Bessone, Mattia; Brazzola, Gregory; Deschner, Tobias; et al.
Abstract: Noninvasive samples as a source of DNA are gaining interest in genomic studies of endangered species. However, their complex nature and low endogenous DNA content hamper the recovery of good quality data. Target capture has become a productive method to enrich the endogenous fraction of noninvasive samples, such as faeces, but its sensitivity has not yet been extensively studied. Coping with faecal samples with an endogenous DNA content below 1% is a common problem when prior selection of samples from a large collection is not possible. However, samples classified as unfavourable for target capture sequencing might be the only representatives of unique specific geographical locations, or to answer the question of interest. To explore how library complexity may be increased without repeating DNA extractions and generating new libraries, in this study we captured the exome of 60 chimpanzees ( Pan troglodytes ) using faecal samples with very low proportions of endogenous content (<1%). Our results indicate that by performing additional hybridizations of the same libraries, the molecular complexity can be maintained to achieve higher coverage. Also, whenever possible, the starting DNA material for capture should be increased. Finally, we specifically calculated the sequencing effort needed to avoid exhausting the library complexity of enriched faecal samples with low endogenous DNA content. This study provides guidelines, schemes and tools for laboratories facing the challenges of working with noninvasive samples containing extremely low amounts of endogenous DNA.